Structural analysis of Iranian educational technologies - Ali Mobini Dehcordi; Seyyed Ahmad Alavi; Hazeline Ayoup (Journal of Global Entrepreneurship Research, 2019)
The purpose of this research is to identify the key driving forces that have an impact on educational technologies to find out the effects of these drivers on each other and the system. This research is a special attention to driving forces which seem they are able to change the educational space paradigms. This study explored the identification of medium term investment opportunities in the field of educational technology. It also helps to plan for the creation and development of new educational institutions and equip universities and schools based on future needs. In this regard, after the identification of effective driving forces, the relationships between these drivers were determined by the experts including university professors, leading educational college managers, and product developers in the field of educational technology and then the results of cross-impact analysis were analyzed by Mick Mac software. Finally, the drivers of virtual learning and learning space as strategic drivers in this space were identified and the factors of reinforcement and system verification indicators were presented.
Keywords: 650; Foresight; Driving force; Educational technology; Structural analysis